The Lung Organ Failure Score (LOFS) as an Early Predictor of Mortality in Blunt Thoracic Trauma: A Preliminary Validation Study in a Southeast Asian Cohort - Charita Ulfah Widyawan; Arie Hasiholan Lumban Tobing; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Blunt thoracic trauma is a leading cause of trauma-related mortality. Early and accurate risk stratification is essential for optimizing outcomes, yet many prognostic scores lack validation in diverse populations. This study aimed to perform a preliminary evaluation of the prognostic value of the lung organ failure score (LOFS) for predicting in-hospital mortality in patients with blunt thoracic trauma in an Indonesian tertiary trauma center. Methods: This retrospective, single-center, exploratory cohort study included adult patients (≥18 years) admitted with blunt thoracic trauma to Dr. Mohammad Hoesin General Hospital from January 2023 to January 2025. Data on demographics, injury characteristics, initial physiological parameters, and clinical outcomes were collected. The LOFS was calculated for each patient. The primary outcome was in-hospital mortality. Statistical analyses included bivariate comparisons, Kendall's Tau correlation, and Receiver Operating Characteristic (ROC) curve analysis. Results: A total of 32 patients were included. The overall in-hospital mortality rate was 21.9% (n=7). The non-survivor group had a significantly higher mean LOFS than the survivor group (21.00±5.29 vs. 14.16±3.92, p=0.001). LOFS demonstrated a moderate, positive correlation with mortality (Kendall's Tau r=+0.568, p=0.001). ROC analysis showed that LOFS had excellent discriminative ability for mortality, with an Area Under the Curve (AUC) of 0.840 (95% CI: 0.685–0.995, p=0.001). An optimal cut-off score of ≥18 yielded a sensitivity of 85.7% and a specificity of 80.0%. Conclusion: In this preliminary study, LOFS was strongly associated with in-hospital mortality and demonstrated excellent discriminative performance. The findings suggest LOFS is a promising and simple tool for early risk stratification in this high-risk population. However, the study's small sample size precluded a reliable assessment of its independence from other risk factors. Further validation in larger, prospective multicenter studies is essential to confirm these findings.